(untitled) (Research, Society and Development, 2021)
This study aimed to describe the epidemiological profile of exogenous intoxications reported in the state of Piauí - Brazil between the years 2013 to 2017. An exploratory, epidemiological and descriptive research was carried out with a cross-sectional, quantitative and retrospective approach, the data were taken from of the National System of Notifiable Diseases (SINAN) of the Unified Health System (SUS), the profile showed a predominance of females, aged between 20-39 years old, incomplete elementary school, the most frequent toxic agent were medicines, circumstances were suicide attempts and evolution with no sequel in most cases. A total of 6,113 cases of poisoning were recorded between the years analyzed. We conclude, with this study, the importance of notifications as a proposal for the implementation of continuous improvements of notifications and the filling of the forms in SINAN, as it will allow us to obtain reliable and consistent data.